DETERMINAN OPINI AUDIT GOING CONCERN - Sihombing, Taruli Risa Kornelia; Amirya, Mirna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to examine the effect of debt default, financial distress, leverage, and opinion shopping on the going concern audit opinion of mining companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2021, involving secondary data obtained from the Indonesia Stock Exchange official website. The samples include 48 companies selected through purposive sampling. The effects among variables in this study are analyzed by logistic regression. This study finds that financial distress negatively affects the acceptance of going concern audit opinion, and leverage positively affects the acceptance of going concern audit opinion. However, debt default and opinion shopping do not affect the acceptance of going concern audit opinion. It implies that an auditor doubts companies’ ability to maintain its sustainability when experiencing financial distress and having a high leverage ratio. In other words, financial distress and leverage can be used as the consideration by an auditor to issue the goingconcern audit opinion.